Peranan dan Sikap Hamba Tuhan Dalam Melaksanakan Misi Gereja Menurut Kisah Para Rasul 20:17-27 - Maria Taliwuna; Alfons Renaldo Tampenawas (Jurnal Teologi Praktika, 2021)
Abstract:Servants of God are messenger of God entrusted by God to carry out God’s mandate on this earth. Therefore, there is no reason for the servants of God not to take an active role in developing, enhancing, and carrying out God’s mission in the church so that the congregation as a church body becomes a missionary congregation. This article used a qualitative method with a literature study approach, as well as a hermeneutic method to examine the discussion in Act. 20:17-27. The purpose of this article was to discovered the principles of servants of God in carrying out the mission of the church according to Act. 20:17-27, and the results of this article showed that carrying out the mission of the church was the responsibility of a servant of God who has been saved by Jesus Christ.  Abstrak:Hamba Tuhan adalah utusan Allah yang di percayakan Allah untuk menjalankan mandat Allah di bumi ini. Oleh sebab itu tidak ada alasan bagi para Hamba-hamba Tuhan untuk tidak berperan aktif dalam mengembangkan, meningkatkan, serta menjalankan Misi Allah di dalam gereja sehingga jemaat sebagai tubuh gereja menjadi jemaat yang misioner. Artikel ini menggunakan metode kualitatif dengan pendekatan studi literatur, serta metode hermeneutik untuk mengkaji pembahasan dalam KIS. 20:17-27. Tujuan dari artikel ini adalah untuk menemukan prinsip-prinsip hamba Tuhan dalam melaksanakan misi gereja menurut KIS 20:17-27, dan hasil dari artikel ini memperlihatkan bahwa melaksanakan misi gereja adalah tanggungjawab dari seorang hamba Tuhan yang telah diselamatkan oleh Yesus Kristus.